2005
DOI: 10.1136/bmj.38483.478183.eb
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of C reactive protein in infections of the lower respiratory tract: systematic review

Abstract: Objectives To evaluate the diagnostic accuracy of C reactive protein in detecting radiologically proved pneumonia and to evaluate how well it can discriminate between bacterial and viral infections of the lower respiratory tract. Data sources Medline and Embase (January 1966 to April 2004), with reference checking. Study selection We included articles comparing C reactive protein with a chest radiograph or with microbiological work-up as a reference test. Two authors independently assessed methodological item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
1
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(137 citation statements)
references
References 46 publications
(58 reference statements)
3
120
1
13
Order By: Relevance
“…Perhaps the inclusion of patients with type III exacerbations would have made this difference more evident. In multivariate analysis, CRP was not predictive of the presence of a PPM in sputum; in a systematic review, testing for CRP was consistently neither sufficiently sensitive to rule out nor sufficiently specific to rule in an infiltrate on chest radiography and a bacterial aetiology of lower respiratory tract infection [27]. In the field of biomarkers, measurement of procalcitonin level shows promise as a means of identifying patients with exacerbations of COPD who require antimicrobial treatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the inclusion of patients with type III exacerbations would have made this difference more evident. In multivariate analysis, CRP was not predictive of the presence of a PPM in sputum; in a systematic review, testing for CRP was consistently neither sufficiently sensitive to rule out nor sufficiently specific to rule in an infiltrate on chest radiography and a bacterial aetiology of lower respiratory tract infection [27]. In the field of biomarkers, measurement of procalcitonin level shows promise as a means of identifying patients with exacerbations of COPD who require antimicrobial treatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 More recently, procalcitonin has emerged as a promising alternative for guiding antibiotic therapy, because this serum marker is elevated in bacterial infections, but not in viral infections or non-specific inflammatory reactions. 16 Procalcitonin has been studied in ambulatory and emergency department settings for guiding antibiotic therapy in adults with ARTIs and been found to reduce antibiotic use and treatment duration without increasing morbidity or mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Improving diagnostic certainty may help identify those patients that will benefit from antibiotic treatment [16][17][18]. A meta-analysis that looked at 13 studies of upper respiratory tract infection (URI) and lower respiratory tract infection (LRTI) on the association between point-of-care (POC) C-reactive protein (CRP) testing and antibiotic prescribing for ARTIs in general practice found that CRP testing significantly decreased antibiotic prescribing at the initial consultation [19].…”
Section: Introductionmentioning
confidence: 99%